Alvaro T. Latorre -Segmentation & Mechanical Characterization of Atherosclerotic Plaques - Latorre, Álvaro T. (Jornada de Jóvenes Investigadores del I3A, 2022)
Segmentation & Mechanical Characterization of Atherosclerotic Plaques